DIPLOMASI VAKSIN INDONESIA DALAM PROGRAM VAKSINASI NASIONAL: SOSIALISASI PENTINGNYA VAKSINASI DAN PENERAPAN PROKES BAGI MASYARAKAT SAMPANG DALAM PENCEGAHAN COVID-19 - Maulidia, Febryanti Nur; Zam Zamy, Mohammad Wildhan Firmansyah; Violando, Wiga Alif; Solikin, Agus (SIYAR Journal, 2023)
For the success of the national vaccination program, Indonesia carries out vaccine diplomacy with various approaches, both bilateral and multilateral and involves all interested parties, with the main objective of opening access to vaccines to achieve the national interest, namely the success of overcoming the COVID-19 pandemic in Indonesia. The existence of a national vaccination program should be able to be followed by all citizens. However, in Sampang Regency, the enthusiasm of the community to vaccinate is very low. In addition, the lack of public awareness of Sampang to implement health protocols is also the cause of the high number of COVID-19 cases in Sampang. This research analyzes the role of Indonesia's vaccine diplomacy in the national vaccination program with a case study of socializing the importance of vaccination and the application of health protocols for the Sampang community in the effort to prevent COVID-19 using descriptive qualitative research methods. Socialization related to the importance of COVID-19 vaccination, the application of health protocols is very much needed to increase public awareness of Sampang in efforts to prevent and handle the COVID-19 pandemic. This socialization can not only be carried out by the government and health workers, but can also be started from oneself, and from the closest environment such as the head of the family or housewife who can carry out socialization in the family environment, among students through various community services, and religious figures through sermons or tausiyah so that the community also has a very important role in fighting the COVID-19 pandemic.